2014
DOI: 10.1371/journal.pone.0103566
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Is Synthesized in Epididymis and Aggregates in a High Molecular Mass Glycoprotein Complex Involved in Sperm-Egg Fertilization

Abstract: The epididymis has an important role in the maturation of sperm for fertilization, but little is known about the epididymal molecules involved in sperm modifications during this process. We have previously described the expression pattern for an antigen in epididymal epithelial cells that reacts with the monoclonal antibody (mAb) TRA 54. Immunohistochemical and immunoblotting analyses suggest that the epitope of the epididymal antigen probably involves a sugar moiety that is released into the epididymal lumen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Albumins are low-molecular weight proteins (about 65 kDa) [71], which are secreted by the testes, epididymides, and prostate. Studies have shown that albumins are implicated in the fertilization-associated events, such as sperm capacitation [72] and the zona pellucida penetration [73]. In one of our previous studies, we have shown that the seminal plasma albumin (ALB) is highly correlated with the motility parameters of stallion spermatozoa [74].…”
Section: Discussionmentioning
confidence: 91%
“…Albumins are low-molecular weight proteins (about 65 kDa) [71], which are secreted by the testes, epididymides, and prostate. Studies have shown that albumins are implicated in the fertilization-associated events, such as sperm capacitation [72] and the zona pellucida penetration [73]. In one of our previous studies, we have shown that the seminal plasma albumin (ALB) is highly correlated with the motility parameters of stallion spermatozoa [74].…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, albumin (ALB) was identified phosphoprotein band with molecular weight of 66 kDa. Albumin seems to be a part of a high molecular mass glycoprotein complex (~260 kDa) that is involved in sperm penetration of the zona pellucida (Arroteia et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, albumins increase the fluidity of the sperm cell membrane during capacitation, and they remove cholesterol and other sterols from the plasma membrane prior to fertilization (Macıas-Garcıa et al 2015). Arroteia et al (2014) found that the sperm membrane contains albumin, which is involved in the penetration of the zona pellucida of egg. The influence of exogenous (but not endogenous) albumin or bovine serum albumin (BSA) on sperm function has been more widely researched, and BSA has been used as a component of sperm capacitation medium.…”
Section: Discussionmentioning
confidence: 99%